THE DEVELOPMENT OF INTERACTIVE ENGLISH MODULE FOR CLASS VIII AT MTS ANNUR BULULAWANG - Ahmad Sulusin; Ahmad Saifudin; Siti Rofi'ah (PROJECT (Professional Journal of English Education), 2023)
The aim of this research is to develop interactive English modules which have been designed in a systematic and attractive manner by containing material, limitations and assessment methods. With this module, researchers hope to help English teachers at MTs An-Nur in the learning process so that they become more active and easy to achieve learning goals. According to observations made by researchers, a problem has been found, namely the lack of student literacy results in very little student interest in learning English. On the other hand students also have difficulty understanding it. The research method used in this article is research and development (R&D), a research approach to produce new products or improve existing products. In producing certain products, this research is a needs analysis using survey or qualitative methods. Each product produced also needs to be tested for product feasibility with experimental methods. In accordance with the results that have been carried out, the validation results obtained by the expert team are 91%. 81% student response, and 85% teacher response. With these results it can be concluded that the development of interactive modules for class VIII at MTs An-Nur Bululawang is declared valid and feasible to use.